Peripheral venous blood gas analysis: An alternative to arterial blood gas analysis for resuscitation and monitoring of critically ill patients. - Ahsan, ASM Areef; Faruq, Mohammad Omar; Fatema, Kaniz; Ahmed, Fatema; Saha, Debasish Kumar; Saha, Madhurima; Nazneen, Suraiya; Sultana, Rozina (Bangladesh Critical Care Journal, 2016)
Objective: This study was aimed to compare between arterial and peripheral venous samples for blood gases and acid base status in critically ill patients and to evaluate if venous sample is a better alternative for initial assessment and resuscitation. Methods: This prospective study was conducted on 50 patients of more than 18 years of age in the department of Critical Care Medicine, BIRDEM General Hospital. Arterial and peripheral venous samples were taken within five minutes of each other and analyzed immediately for blood gases and acid base status. Mean difference and Pearson's product moment correlation coefficient was used to compare the result. Results: Mean difference and correlation coefficient between arterial and peripheral venous sample for pH, bicarbonate, base excess, PaCO2 and TCO2 value showed high correlation (r > 0.9). Comparison of electrolyte and hematocrit between arterial and peripheral venous sample also showed high correlation (r > 0.9). Conclusion: Peripheral venous gas analysis for pH, bicarbonate, base excess, PCO2 and Electrolytes (Na+, K+) show good correlation with the respective arterial values. This result suggests that venous estimations can be an acceptable alternative to arterial measurements for managing critically ill patients. Bangladesh Crit Care J September 2016; 4 (2): 92-95